Effect of waxing on the storage behavior of carabao mangoes (Mangifera indica L. var. Carabao) - Santiago, Elena P.; De Leon, Sonia Y. (1966)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fruit -- Waxing; Mango -- Storage